N-(3-Methylphenyl)quinoxalin-2-amine monohydrate - Ariffin, Azhar; Tiekink, E.R.T.; Idris, A.; Abdullah, Z.; Fairuz, Z.A.; Ng, S.W. (International Union of Crystallography, 2010)
The quinoxaline system in the title hydrate, C(15)H(13)N(3)center dot H(2)O, is roughly planar, the r.m.s. deviation for the 18 non-H atoms being 0.188 angstrom; this conformation features a short intramolecular C-H center dot center dot center dot N(pyrazine) interaction. In the crystal, the amine H atom forms an N-H center dot center dot center dot O hydrogen bond to the water molecule, which in turn forms two O-H center dot center dot center dot N hydrogen bonds to the pyrazine N atoms of different organic molecules. These interactions lead to supramolecular arrays in the bc plane that are two molecules thick; additional pi-pi interactions stabilize the layers [ ring centroid-centroid distance = 3.5923 (7) angstrom]. The layers stack along the a-axis direction via C-H center dot center dot center dot pi contacts.